Perceptions about the concept of the nation: diagnosis through the literary contribution of Juan León Mera and the decolonial proposal - Viñamagua Quezada, Glenda (2020)
From the literary as well as the art in general, its critical position is relevant, arising as a response to the events that manifest at the social level in order to question the established system and achieve transformations. This work is understood as the commitment that intellectuals should acquire throughout history. In this case, an approach will be made to the position of Juan León Mera regarding the creation and understanding of the concept of nation through the composition of the lyrics of the National Anthem of Ecuador. It will be exposed from the theory approach such as decolonialism and heart, an alternative of inclusive spaces, assumed as a challenge for society to be approached and disseminated from education. The objective of this article is to reflect on the idea of ​​nation and its construction from the exclusion of the other due to the process of colonization as a way to counteract this thought; for this a documentary bibliographic research has been carried out from a hermeneutical perspective. The contribution of this research lies in focusing on decolonial theory as an alternative to awaken awareness towards the claim in communion with otherness through literary and educative work.